First synthesis of a noreremophilane isolated from the roots of ligularia przewalskii - Reddy, D. Srinivasa; Palani, K.; Balasubrahmanyam, D.; Kamath, V. B.; Iqbal, Javed (Tetrahedron Letters, 2005)
The total synthesis of a natural product noreremophilane has been achieved in just three steps from readily available starting materials. A highly stereo- and regio-selective Diels-Alder reaction was the key step in Our synthesis. (c) 2005 Elsevier Ltd. All rights reserved.